Recent progress in quantum dots based nanocomposite electrodes for rechargeable monovalent metal-ion and lithium metal batteries. Issue 2 (14th December 2021) - Puttaswamy, Rangaswamy; Pai, Ranjith Krishna; Ghosh, Debasis
Abstract : This review summarizes the recent progress in quantum dot based nanocomposites as electrode materials in Li/Na/K-ion batteries, as cathodes in Li–S and Li–O2 batteries and in improving the electrochemical performance of Li metal anode batteries. Abstract : Engineering electrode architecture with an abundant active surface for charge storage, shorter ion diffusion path, low charge transfer resistance, and structural integrity against volume change during cycling are the key requirements while designing electrodes in rechargeable batteries. Compared to the traditional micro or nano size of active materials, quantum dots (QDs) with ultrafine particle size (<10 nm) offer a large number of active edges as well as large accessible surface area, shorter ion diffusion path, excellent dispersibility, and homogeneous volume expansion/contraction to buffer lattice distortion during cycling. Apart from acting as active materials, they can also act as electrocatalysts to accelerate certain kinetically sluggish redox reactions or regulate metal deposition at the anode during charging. However, due to the high surface charge, QDs tend to aggregate, and often require a suitable support and rational designing to prevent this aggregation and to retain the unique properties of QDs as electrode materials in the solid state. In addition, such hetero-structures can also modify the physicochemical behavior and electrochemical performance of a composite material. Herein we represent a timely review on the recent advancement in QD based carbonaceous and noncarbonaceous nanocomposite electrodes for rechargeable monovalent metal-ion (Li, Na, and K-ion), and lithium–metal (Li–S and Li–air) batteries. Different strategies adopted towards fabricating high-performance electrodes with QDs, such as (i) decorating conducting carbon (graphene) QDs on nano/micron-sized active materials, (ii) engineering active material QDs on conducting carbon supports, and (iii) creating active materials QD/active material heterostructures with or without an additional conducting phase, etc. along with their electrochemical performances have been summarized. In addition, we have also commented on possible future research directions employing QDs.